Cast Down, But Not Forsaken: The Second World War Experience and Memory of German-Canadian Lutherans in Southwestern Ontario - Worsfold, Elliot (Ontario History)

(untitled) (The Ontario Historical Society, 2014)
This study seeks to reassess the notion that German-Canadians in Ontario were “silent victims” during the Second World War by exploring the wartime experience and memory of German-Canadian Lutheran congregations in Oxford and Waterloo Counties. Far from silent, Lutheran pastors initiated several strategies to ensure their congregants did not face discrimination and internment as they had during the First World War. These strategies encompassed several reforms, including eliminating German language church services and embracing English-Canadian symbols and forms of post-war commemoration. However, these reforms were often met with resistance and ambivalence by their congregations, thereby creating a conversation within the German-Canadian Lutheran community on how to reconcile its Germanic and Lutheran heritage with waging a patriotic war. While previous studies have primarily focused on identity loss, this study suggests that the debates that occurred within these Lutheran churches were representative of the community’s German-Canadian hyphenated identity.